2020
DOI: 10.1007/s00405-020-06211-4
|View full text |Cite
|
Sign up to set email alerts
|

The predictive factors for postoperative hypoparathyroidism and its severity on the first postoperative day after papillary thyroid carcinoma surgery

Abstract: Purpose The purpose of the study was to investigate the predictive factors for hypoparathyroidism and its severity on the first postoperative day (POD1) after total thyroidectomy (TT) with or without central neck dissection (CND) in patients with papillary thyroid carcinoma (PTC). Methods From February 2014 to February 2019, 2550 PTC patients were admitted to our department. PTC patients who underwent TT were enrolled in this study. A parathyroid hormone (PTH) level lower than 15 pg/mL on POD1 was defined as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Both retrospective studies found bilateral CND was associated with a significantly increased rate of transient hypoparathyroidism. However, another retrospective study of 690 TT patients found a different result after controlling other confounding factors [ 17 ]. Huang et al [ 17 ] showed the extent of CND was not independently associated with postoperative hypoparathyroidism after adjusting for other confounding factors such as surgeon, intraoperative carbon nanoparticle injection, and preoperative PTH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both retrospective studies found bilateral CND was associated with a significantly increased rate of transient hypoparathyroidism. However, another retrospective study of 690 TT patients found a different result after controlling other confounding factors [ 17 ]. Huang et al [ 17 ] showed the extent of CND was not independently associated with postoperative hypoparathyroidism after adjusting for other confounding factors such as surgeon, intraoperative carbon nanoparticle injection, and preoperative PTH.…”
Section: Discussionmentioning
confidence: 99%
“…However, another retrospective study of 690 TT patients found a different result after controlling other confounding factors [ 17 ]. Huang et al [ 17 ] showed the extent of CND was not independently associated with postoperative hypoparathyroidism after adjusting for other confounding factors such as surgeon, intraoperative carbon nanoparticle injection, and preoperative PTH. In our study, neither bilateral CND nor LND was statistically associated with postoperative hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations